Avaliação do comportamento de ligações mistas viga-pilar e viga-viga, em temperatura ambiente e em situação de incêndio, e seus efeitos no comportamento da estrutura - Nicoletti, Renato Silva (2023)
Steel-concrete composite connections are those in which the transfer of forces between structural elements, as well as stiffness and strength, are simultaneously ensured by steel and concrete components and elements. At room temperature, the behavior of steel-concrete composite connections is well known. However, the behavior of these connections in fire situations and their effects on the structure still need to be further investigated. This study investigated, through numerical analyses, the behavior of beam-beam and beam-column composite connections in steel and concrete, both at room temperature and in fire situations, as well as their effects on the overall structural behavior. Initially, a bibliometric analysis and subsequent systematic review of the literature regarding studies involving steel-concrete composite connections in fire situations were conducted to identify the main knowledge gaps in the field. Subsequently, numerical models of steel and steel-concrete composite connections were constructed and validated under both room temperature and fire conditions. Subsequently, a parametric analysis was conducted, simulating 663 numerical models of composite connections under both ambient temperature and fire conditions. The variables under study encompassed connection type, beam and column profiles, negative reinforcement ratio of the composite connection, degree of steel-concrete interaction between the composite beam and slab, slab type, direction of moment curvature at the connection, steel strength, and concrete strength. All parametric variables exerted influence on connection behavior. Fire conditions revealed distinct failure mechanisms compared to those observed under ambient temperature for all connection types. Practical equations were formulated for calculating moment resistance and initial stiffness at ambient temperature, as well as minimum stiffness during a fire and cumulative rotation variation, specifically for beam-column composite connections. Subsequently, to evaluate the impact of connections on the fire behavior of structures, 8 building models were constructed. In these analyses, significant influence of the number of stories and fire location on building behavior was observed. Moreover, the fire resistance duration of the buildings exceeded that of isolated connection models, reinforcing the importance of considering the global behavior of structures, along with proper interactions among elements, in fire situation design.